The effectiveness of self-regulated strategy development instruction for improving writing abilities in a school-age child with cochlear implants: A single subject research design study. (2nd January 2021) - Rice Aberth, Jessica; Werfel, Krystal L.
ABSTRACT: Objectives: The two-fold purpose of this feasibility study was to determine if (a) self-regulated strategy development intervention would improve the writing skills of a child who uses cochlear implants and (b) if self-regulated strategy development intervention would improve the reading comprehension skills of a child who uses cochlear implants. Methods: One eleven year-old child with bilateral sensorineural hearing loss who utilised bilateral cochlear implants participated in this single-subject, multiple baseline across behaviours design treatment study which examined the effectiveness of using writing intervention to improve reading comprehension in children who are deaf. The participant completed three seven-week writing interventions focused on narratives, opinion essays, and persuasive essays. The participant also completed progress monitoring in baseline, intervention, and maintenance conditions for each behaviour. Intervention was delivered one-on-one for 60 min one day per week. Results: Visual analysis of progress monitoring data indicated that writing performance improved in two out of the three styles of writing throughout the intervention and that the improvement for those two areas was maintained after intervention was complete. Comparison of pre- and post-test measures of reading comprehension indicated that the writing intervention was effective for improving reading comprehension for the participant. Conclusion: Self-regulated strategy development writing intervention may be a beneficial intervention strategy to improve writing skills, and potentially reading comprehension skills, in children who are deaf and use cochlear implants.